Open Assessment of Learning: A Meta-Synthesis - Chiappe, Andrés; Pinto, Ricardo; Arias, Vivian (International Review of Research in Open and Distributed Learning, 2016)
Open Assessment of Learning (OAoL) is an emerging educational concept derived from the incorporation of Information and Communication Technologies (ICT) to education and is related with the Open Education Movement. In order to improve understanding of OAoL a literature review was conducted as a meta-synthesis of 100 studies on ICT-based assessment published from 1995 to 2015, selected from well-established peer-reviewed databases. The purpose of this study focused on identifying the common topics between ICT-based assessment and OAoL which is considered as an Open Educational Practice.The review showed that extensive use of the Internet makes it easy to achieve some special features of OAoL as collaboration or sharing, which are considered negative or inconvenient in traditional assessment but at the same time become elements that promote innovation on that topic. It was also found that there is still a great resistance to accept change (as OAoL does) when structural elements of traditional assessment are questioned or challenged.